Evaluation of Bone Density in Ankylosing Spondylitis Patient on Biologic Agents in Erbil City Case Control Study - Ibrahim Rasul , Mohammed; Kader Media, Shwan (Diyala Journal of Medicine, 2021)
Background: Ankylosing spondylitis is a chronic autoimmune inflammatory disease, mostly affect young men. Reduced bone density is the most common complication in ankylosing spondylitis, since reduced bone density occurs in most of the patients. Assessment of bone density in the early stages of the disease by using X- ray absorptiometry is essential. Objective: To determine and evaluate the bone mineral density of ankylosing spondylitis patients compared healthy to control group. Patients and Methods: This is a cross-sectional case control study of 50 patients with ankylosing spondylitis according to the Modified New York criteria and 50 healthy control group. The data were collected including socio demographic information of all patients (age, gender, medical history); systemic diseases type of biology treatment, using supplements, duration of ankylosing spondylitis, regular exercise, and smoking. The body mass index was calculated. Bone mineral density of the lumbar spine (L1-L4), and the left femoral neck were measured by using a dual energy x-ray absorptiometry. Statistical analysis was done by using a statistical package for social sciences (SPSS) version 22; Fisher’s exact, and Student’s t tests were used to compare two means. A p value of ≤ 0.05 was considered statistically significant. Results: The prevalence of osteoporosis and osteopenia among patients group according to T-spine score were 12% and 42% respectively, compared with 0% and 26% respectively among the control group (p= 0.002) which was statistically significant. According to the T-left femur none patients group and the control group had osteoporosis, but 46% of the cases had osteopenia, compared with 8% of the controls which was statistically significant. There was a significant but non-consistent association between the disease duration and the osteoporosis, and osteopenia in spine and femur. The prevalence of osteopenia and osteoporosis in the spine and femur were highest among those with low body mass index. Conclusion: Osteoporosis and osteopenia are common among patients with ankylosing spondylitis. In the early stage of disease osteoporosis can occur. The osteoporosis of the spine is more common than in the femur. Osteoporosis related to the duration of the diseases and body mass of the patient.